Physico-chemical and Mineralogical Properties of Fly Ash from Thermal Power Stations in Northern Vietnam - Le, Van Thien (ĐHQGHN, 2017)
Fly ash is produced as a result of coal combusion at high temperatures in thermal power stations and discharged in ash ponds which absorb huge amount of water, energy, and land area. As the demand for power increases, the amount of fly ash from thermal power stations in Northern Vietnam is increasing year by year. Therefore, the environmental friendly fly ash management would remain a great concern. In this paper, physico-chemical and mineralogical properties of fly ash from Pha Lai, Mong Duong and Ninh Binh thermal power stations were studied for ultilization to improve soil properties. Results shows that the properties of fly ash depend on the nature of parent coal, conditions of combustion, type of emission control devices, and storage and handling methods. The fly ash samples occur 1-8 µm in particle size and rounded to angular in shape. They are alkaline (pHKCl >9) and CEC considerably ranged from 8.44 meq/100 g to 8.68 meq/100 g. All samples comprised of Mg, Al, Si, P, S, K, Ca, Ti, Cr, Mn, Fe, Ni, Cu, Zn, Rb and Pb with the highest contents of Al and Si. Of which, the highest content of Al and Si presents in fly ash sample from Pha Lai and Ninh Binh, respectively. High contents of K, P, Ca, Mg, S and some micro-nutrients are also found in fly ash samples. However, they have very low contents of radioactive elements (226Ra, 238U, 232Th, 40K) and heavy metals. Besides, fly ash contains minerals such as quartz (SiO2) and mullite (Al2Si2O13).